Procesos administrativos, en la distribuidora de Confites E.F de la ciudad de Babahoyo, ubicado en el Cantón Babahoyo-Provincia de Los Ríos, periodo 2022 - Estupiñán Figueroa, Desiree Ibeth (2023)
In today's business era, where competition is fierce and customer expectations are constantly rising, operational efficiency and quality customer service are crucial to the success and sustainability of any business. A case that illustrates the importance of addressing these challenges is that of Distribuidora de Confites E.F, located in the picturesque Babahoyo Canton of the Province of Los Ríos. Throughout 2022, this company has faced a substantial problem that has left scars in its ability to provide quality service and maintain customer satisfaction. One of the main problems identified is the management of customer queries and requests. The significant delay in responding to these queries has led to frustration and discontent, eroding customer trust in the company. This delay can have deep roots in a lack of internal coordination, inadequate resource allocation, or ineffective communication processes. In addition, the use of a centralized system for monitoring consultations has resulted in untimely and less efficient attention. Another crucial aspect that has negatively impacted Distribuidora de Confites E.F is poor order management. Customers have complained about the lack of follow-up on their orders, some of which are not delivered within the agreed deadlines. This situation has led to a loss of confidence in the company and has exposed problems in the supply chain, lack of coordination between teams and difficulties in the packaging and shipping process. In this case study, we will explore each of these challenges in depth and present practical solutions to address them. Distribuidora de Confites E.F has undeniable potential to overcome these obstacles and strengthen its position in the market.